2015
DOI: 10.1038/srep17434
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression analysis offers new insights into the origin and evolution of Physcomitrella patens stress response

Abstract: Changes in the environment, such as those caused by climate change, can exert stress on plant growth, diversity and ultimately global food security. Thus, focused efforts to fully understand plant response to stress are urgently needed in order to develop strategies to cope with the effects of climate change. Because Physcomitrella patens holds a key evolutionary position bridging the gap between green algae and higher plants, and because it exhibits a well-developed stress tolerance, it is an excellent model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…mat clearly showed that the top layer had a higher metabolic turnover compared with the cells from the bottom layer and exhibited acclimation to light and UVR, and in general stress protection. The induction of stress-related transcript changes observed here are very similar to observations in the charophytes Coleochaete and Spirogyra (Timme and Delwiche, 2010), the moss Physcomitrella (Khraiwesh et al, 2015), pointing out the evolutionary significance of our findings.…”
Section: Discussionsupporting
confidence: 88%
“…mat clearly showed that the top layer had a higher metabolic turnover compared with the cells from the bottom layer and exhibited acclimation to light and UVR, and in general stress protection. The induction of stress-related transcript changes observed here are very similar to observations in the charophytes Coleochaete and Spirogyra (Timme and Delwiche, 2010), the moss Physcomitrella (Khraiwesh et al, 2015), pointing out the evolutionary significance of our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Using RNA-Seq data with high representation of orphan gene expression dramatically improves the efficacy of gene prediction by MAKER, by the Direct Inference pipeline, and by the BIND and MIND combination pipelines. Thus, the accuracy of an initial genome annotation will be maximized by selecting RNA-Seq data from diverse samples, including samples that typically express high levels of young genes, e.g., reproductive tissues and stressed tissues 10,14,54,[72][73][74][75][76][77][78]83 . Additionally, reannotation 70,84,85 outcomes can be optimized by utilizing evidence from diverse samples in the expanded body of public RNA-Seq datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The "orphan-rich" dataset is designed to maximize orphan gene representation. We reasoned that selecting samples which contain a breadth of orphan gene transcripts could be important because many, though by no means all 10 , orphans are highly expressed under only a very limited set of conditions 10,14,54,[72][73][74][75][76][77][78] . The "orphan-rich" RNA-Seq samples were chosen from over a thousand samples in SRA; over 60% of all Araport11-annotated orphans are transcribed in each sample.…”
Section: Rna-seq and Protein Used As Extrinsic Evidence For Gene Predmentioning
confidence: 99%
“…It has already been applied in the study of clinical diseases (Khraiwesh et al, 2015). It detects the whole genome of the objects, which may provide possible therapeutic effect and clarify the mechanism.…”
Section: Discussionmentioning
confidence: 99%